A new species of Heteropsylla Crawford from Ecuador with new host-plant and distribution records for the genus (Homoptera, Psylloidea). - Hodkinson, Ian D.; Muddiman, Stephen B. (Contributions to Entomology = Beiträge zur Entomologie, 1993)
Heteropsylla pulchella spec. nov. is described from Ecuador. Additional host-plant and distribution records are given for Heteropsylla bidentata, H. cubana, H. truncata, H. obscura and H. spinulosa. Nomenclatural Acts pulchella Hodkinson & Muddiman, 1993 (Heteropsylla), spec. n.